Proposal of Air Supply Smoke Control System about Stair-case Considering Stack Effect & Opening of the Outside Door - Kim, Yongkwang (Fire Science and Engineering, 2020)
Most of the special escape staircase smoke control systems for high-rise buildings in accordance with the national fire safety code NFSC 501A are constructed with smoke control only vestibule, making it difficult to expect a proper role in an emergency. This standard, which was created by introducing the concept of air supply pressurized smoke control 25 years ago, created Korea´s smoke control only vestibule, which was not found in developed countries, and has been mainly applied to it to fit into the poor architectural environment of the time. However, there is a fundamental flaw there, so the performance test for completion without occupants is passed, but in the presence of occupants, the performance does not come out properly and it is being blamed for being useless. In this regard, the author proposes a method of air supply pressurized smoke control for stair-case that avoid the smoke control method only vestibule, reduces the stack effect with good cost-effectiveness, and considers opening the outside entrance door of the stair-case.